The Paradox of Digital Transparency in the Implementation of Open Government in Gowa Regency - Peby Wayasirli Amriani; Sangkala Sangkala; M. Thahir Haning; Muhammad Yunus (Journal Social Civilecial, 2026)
This study examines the paradox of digital transparency in the implementation of Open Government in Gowa Regency, South Sulawesi, where strong digital infrastructure has not fully produced substantive public information disclosure. Using a qualitative case study design, the research explores how technological capacity, organizational responsiveness, and cross-sectoral coordination shape transparency outcomes within the Public Information and Documentation Officer (PPID) system. Data were collected through in-depth semi-structured interviews with seven key informants, consisting of the Main PPID and Assistant PPID administrators from strategic regional agencies, and through document analysis of public information service reports, regulatory documents, standard operating procedures, and PPID data from 2021 to April 2026. The findings show that Gowa Regency has achieved digital sovereignty through an independently managed server and integrated PPID portal, enabling broader formal access to information. However, transparency remains largely procedural due to a 39 percent cumulative rejection rate of information requests, role ambiguity among PPID administrators, fragmented human resource capacity, and weak synchronization between the Main PPID and Assistant PPIDs. The study reveals that digital platforms function more as symbolic instruments when not supported by dedicated personnel, clear institutional roles, responsive procedures, and integrated data governance. These findings confirm that Open Government cannot be realized through technology alone but requires organizational capacity and managerial accountability. The study recommends strengthening functional information management positions, improving inter-agency data integration, and institutionalizing responsive service standards to transform digital transparency into substantive public accountability. The results contribute to local governance studies and practical reform in Indonesia and beyond.